2014
DOI: 10.1111/febs.12857
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical characterization of the folyl‐poly‐γ‐l‐glutamate hydrolyzing activity of human glutamate carboxypeptidase II

Abstract: In addition to its well-characterized role in the central nervous system, human glutamate carboxypeptidase II (GCPII, Uniprot ID Q04609) acts as a folate hydrolase in the small intestine, participating in the absorption of dietary polyglutamylated folates (FolGlun), which are the provitamin form of folic acid (also known as vitamin B9). Despite the role of GCPII as a folate hydrolase, nothing has been known about the processing of polyglutamylated folates by GCPII at the structural or enzymological level. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…B,C). These results are in good agreement with previously reported structural data showing that GCPII is unable to fully utilize the ABS for binding of the pteroate moiety of FolGlu 1 , while the FolGlu 2–3 substrates are able to bind into this exosite .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…B,C). These results are in good agreement with previously reported structural data showing that GCPII is unable to fully utilize the ABS for binding of the pteroate moiety of FolGlu 1 , while the FolGlu 2–3 substrates are able to bind into this exosite .…”
Section: Resultssupporting
confidence: 93%
“…A. The glutamate moiety of BCG binds into the S1′ pocket of GCPII in an identical manner as described for FolGlu n or NAAG substrates . It forms hydrogen bonds with the side chains of Arg210, Asn257 and Tyr552, and also with Lys699 and Tyr700 forming the so‐called ‘glutarate sensor’ .…”
Section: Resultsmentioning
confidence: 99%
“…Of interest, our laboratory recently found that GCPII is highly upregulated in microglial cells (e.g., the immune cells of the brain) following inflammation and its inhibition prevents neurological damage (27). With respect to enzymatic mechanism, to date there are 3 known FOLH1 /GCPII substrates that could be implicated as possible mediators of the therapeutic effect, including N-acetylaspartylglutamate (NAAG) (28), folate polyglutamate (2931), and laminin-derived peptides (32, 33). NAAG is one of the most abundant peptides in nervous tissues where it is thought to participate in glutamatergic transmission, acting through NMDA and mGlu3 receptors (20, 34, 35).…”
Section: Discussionmentioning
confidence: 99%
“…NAAG is the most abundant neuropeptide in the brain and is thought to act as a reservoir for GCPII-dependent release of the neurotransmitter L-Glu. In the brush border of the small intestine the same enzyme also exerts folyl-poly-g-Glu carboxypeptidase activity, which is thought to mediate dietary folate uptake (Pinto et al, 1996;Navrátil et al, 2014). The in vivo requirement of these biochemical activities could not be clearly demonstrated since knock-out mice of GCPII show normal development and behavior, most likely because of functional redundancy with the close paralog GCPIII (Bacich et al, 2002;Gao et al, 2015).…”
mentioning
confidence: 99%